Contribution Of Organizational Climate, Emotional Intelligence and Professional Competence to Teacher Work Effectiveness - Yusrina Yusrina (Indonesian Journal of Education (INJOE), 2021)
Social changes are so fast, causing various problems and challenges to also change, including in terms of competence experienced by teachers. The study conducted in this study is a library by collecting various theories, where the results of the study show that the organizational climate in which the teacher lives affects the emotional intelligence of the teacher concerned